Narrating ‘Home’ in Early Christian Biography: Athanasius’ Life of Antony and Its Literary Predecessors - De Cock, Miriam (Religions, 2024)
In this paper, I provide a close examination of early Christian biographical sources through the heuristic lens of “home studies”, tracing a thread from the New Testament Gospels to martyrdom texts, the apocryphal Acts literature, Eusebius’ biography of Origen in his Church History, and finally, Athanasius’ Life of Antony. I demonstrate that the lens of home allows us to see that in each of these discrete groups of texts, Christ’s call to discipleship is understood to redefine and reconstitute the meaning of home and relatedly, family: to be “home” required a great deal of displacement and mobility as one forsook one’s biological family and household for the sake of obedience to the call of Christ. I argue that three topics, typically examined separately, are fruitfully brought together through the lens of home: (1) the shaping of ancient Christian identity formation, as expressed by the characters’ use of familial language to identify other members of the early Christian movement; (2) the mobile nature of the person who joins the movement, providing insights about the mobility and travel of many of its members; and (3) ancient Christian eschatological thought concerning the final dwelling of Christ-believers in some form of otherworldly home after death.